Comparing the Effects of Lavender and Lemon Aromatherapy on Pain Levels in Women with Caesarean Section Patients - Juwitasari; Ririn Harini; Nurhasanah (Universitas Negeri Surabaya, 2025)
Background: Pain is a common postoperative experience for women following Caesarean section, typically occurring around the surgical site and lasting from the first 48 hours and can be persisted until three weeks or more. Unmanaged pain can lead to increased morbidity, reduced functionality and quality of life, and delayed recovery. Aromatherapy, specifically lavender and lemon, may offer non-pharmacological approaches to alleviate postoperative pain. Purpose: This study investigated the effects of lavender and lemon aromatherapy on pain levels among post-caesarean section patients in the first and second day of post caesarean section. Method: A quasi-experiment, non-equivalent control group design was applied, involving 36 participants which are divided in two groups. Group A (n=18) received Lavender Aromatherapy as an intervention, and group B (n=18) received Lemon Aromatherapy as a control. Pain levels were measured using a Numeric Rating Scale (pain level 1-10). Data were analysed using paired sample t-tests and independent sample t-tests. Results: In the lavender group, average pain scores decreased from 5 at pre-test to 4 at post-test. Similarly, in the lemon group, pain scores decreased from 6 at pre-test to 4 at post-test. Both lavender and lemon aromatherapy significantly reduced pain levels (p < 0.001, p < 0.05, respectively). However, there was no significant difference in pain relief between the two interventions (p = 0.584). Conclusion: Both lavender and lemon aromatherapy significantly reduce pain levels in women after Caesarean section. Either intervention may be considered as a non-pharmacological option for managing post-Caesarean section pain. Keywords :Aromatherapy, Caesarean Section, Lavender, Lemon, Pain Level.